Management of the polyallergic patient with allergy immunotherapy: a practice-based approach. Issue 1 (December 2016) - Demoly, Pascal; Passalacqua, Giovanni; Pfaar, Oliver; Sastre, Joaquin; Wahn, Ulrich
Background The great majority (60–80 %) of patients consulting specialist physicians for allergic respiratory disease are polysensitized and thus may be potentially clinically polyallergic. However, management approaches to allergen immunotherapy (AIT) in polysensitized and polyallergic patients are not standardized. Methods An international group of clinicians with in-depth expertise in AIT product development, clinical trials and clinical practice met to generate up-to-date, unambiguous, pragmatic guidance on AIT in polysensitized and polyallergic patients. The guidance was developed after reviewing (1) the current stance of regulatory bodies and learned societies, (2) the literature data on single- and multi-AIT and (3) the members' confirmed clinical experience with polysensitized patients. Results AIT is safe and effective in polysensitized and polyallergic patients, and should always be based on the identification of one or more clinically relevant allergens (based on the type and severity of symptoms, the duration of induced symptoms, the impact on quality of life and how difficult an allergen is to avoid). Single-AIT is recommended in polyallergic patients in whom one of the relevant allergens is nevertheless clearly responsible for the most intense and/or bothersome symptoms. Parallel 2-allergen immunotherapy or mixed 2-allergen immunotherapy is indicated in polyallergic patients in whom two causal relevant allergens have a marked clinical and QoL impact. In parallel 2-allergen immunotherapy (whether subcutaneous or sublingual), high-quality, standardized, single-allergen formulations must be administered with an interval of 30 min. Mixing of allergen extracts may be considered, as long as (1) the mixture is technically feasible, (2) the mixture is allowed from a regulatory standpoint, (3) the allergen doses are reduced in proportion to the number of components but are still at concentrations with demonstrated efficacy. Conclusions Physicians can prescribe AIT (preferably with high-quality, standardized, single-allergen formulations) with confidence in polysensitized and polyallergic patients by focusing on clinical/QoL relevance and safety.